2015
DOI: 10.2134/cs2015-48-5-2
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen management for grain yield and protein in the Northern Great Plains

Abstract: The single most important thing a grower can do to get record wheat yields is improve nitrogen (N) management.1 Optimum N management for increased grain yield and protein includes: basing N rates on realistic yield potential, knowing the soil residual N, determining application rate and timing, and using appropriate placement and N sources. The steps are the same for all regions, but decisions should be based on guidelines specific to a grower's area. Earn 1 CEU in Nutrient Management by reading this article a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 4 publications
0
18
0
Order By: Relevance
“…Growing wheat with high grain protein begins with selecting of appropriate genotypes followed by management practices [ 32 ]. Therefore, the information about genetic diversity for this trait is important.…”
Section: Discussionmentioning
confidence: 99%
“…Growing wheat with high grain protein begins with selecting of appropriate genotypes followed by management practices [ 32 ]. Therefore, the information about genetic diversity for this trait is important.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in a study conducted in South Australia, Grace [ 49 ] found that natural mycorrhization of barley was between 9 and 47% in different field sites. Compared to the vesicles, the high percentage of arbuscules observed in the roots of barley at the “Heading” stage could be explained by the high nutrient demand of the plants for grain filling [ 50 ]. Vesicles serve as storing organs for lipids and other energy reserves [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on technical recommendations (Cohan and Bouthier, 2010), and data from several studies (e.g. Limaux et al, 1999;Jones et al, 2013;Kissel et al, 2004), we defined that conditions were optimal for fertilizer application (i) each day followed by a cumulative rainfall exceeding 10 mm within three days, or (ii) each day with a positive difference between cumulative rainfall and potential evapotranspiration over the last five past days. Moreover, as Recous and Machet (1999) showed that most of the N-fertilizer applied is taken up by the crop within seven to fourteen days after application, we fixed the minimum interval between two consecutive N applications at 15 days.…”
Section: Simulation Of Various Sequences Of N-fertilizer Application ...mentioning
confidence: 99%
“…Nevertheless, applying N fertilizer during a rainfall event strongly limits N losses by volatilization (Meyer et al, 1961;Powlson et al, 1992;Campbell et al, 1995;Jones et al, 2013), the process responsible for the largest amount of N losses (Limaux et al, 1999).…”
Section: Putting Into Practice the New Way Of Managing N-fertilizationmentioning
confidence: 99%